3D printing soft package battery based on composite solid electrolyte design

By introducing a composite solid electrolyte (M-CSE) layer into an all-solid state battery, the interface instability and lithium dendrites of sulfide solid electrolyte and lithium metal negative electrode are solved, and the stability and long-cycle performance of the battery are improved under high current density.

CN119890426AActive Publication Date: 2025-04-25LIYANG ZHONGKE GUNENG NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510154228.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-25
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The combination of sulfide solid electrolyte and lithium metal negative electrode has problems such as chemical instability in interface, growth of lithium dendrites and narrow electrochemical windows, which affects the performance and safety of the battery.

Method used

A composite solid electrolyte (M-CSE) was designed to prepare by refinement mixing, including LPSCl and LSiSnPSBrO, and the M-CSE layer was prepared by ball milling to enhance the inhibition ability and interface stability of lithium dendrites.

Benefits of technology

Under high current density conditions, the M-CSE layer significantly improves the stability and long cycle performance of lithium batteries, extends the service life of the battery, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890426A_ABST
    Figure CN119890426A_ABST
Patent Text Reader

Abstract

The invention discloses a 3D printing soft package battery based on composite solid electrolyte design, and relates to the technical field of solid state batteries, the composite solid electrolyte (M-CSE) comprises the following components: LPSCl and LSiSnPSBrO; according to the M-CSE structure, it is guaranteed that in the electrolyte decomposition process, internal expansion stress generates compression force on adjacent electrolytes, further decomposition is effectively inhibited, the self-limiting behavior is beneficial to forming a thin and compact interface layer, interface impedance is remarkably reduced, and lithium dendrites are prevented from permeating; the decomposition of LSiSnPSBrO not only produces metastable electrolyte particles, but also results in the formation of a lithium-philic Li-Si / Sn alloy that acts as a stone-philic seed in M-CSE, enhances lithium kinetics and regulates lithium nucleation, resulting in uniform lithium deposition, and the M-CSE interface structure contributes to balancing the electric field and optimizing lithium deposition, significantly improving the overall performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-solid-state batteries, and in particular to a composite solid-state electrolyte and a preparation method thereof, which are specifically applied to all-solid-state batteries, and also to an all-solid-state battery comprising the composite solid-state electrolyte and a preparation method thereof, and to a 3D printed soft-pack battery comprising the composite solid-state electrolyte and a preparation method thereof. Background Art

[0002] Although the combination of sulfide solid electrolyte and lithium metal anode has great potential in improving battery energy density and safety, it still faces many technical challenges.

[0003] First, interfacial chemical instability is a key issue. Sulfide electrolytes are prone to uncontrollable chemical reactions when in contact with lithium metal, generating non-conductive byproducts such as Li2S and Li3P, which increase interfacial impedance and seriously affect the ion transport performance and overall electrochemical performance of the battery. In addition, the high activity of lithium metal will further aggravate these side reactions, making it difficult to maintain interfacial stability, especially under high voltage working conditions, the electrolyte may also be oxidized or decomposed, affecting the cycle life.

[0004] Another significant problem is the growth of lithium dendrites. Although solid electrolytes can theoretically inhibit the formation of dendrites, at high current density, lithium dendrites may still grow and pierce the electrolyte, causing internal short circuits and seriously affecting the safety of the battery. Lithium metal undergoes large volume changes during deposition and stripping, which can lead to poor interfacial contact with sulfide electrolytes, resulting in voids and inhomogeneities, further exacerbating dendrite growth and interfacial failure. In addition, the electrochemical window of sulfide solid electrolytes is narrow. When the battery operates at a higher voltage, the electrolyte is prone to oxidation or reduction reactions, producing irreversible byproducts. This limits the pairing of this type of electrolyte with high-voltage positive electrode materials, affecting the energy density and operating stability of the battery.

[0005] Finally, in terms of manufacturing, sulfide solid electrolytes are very sensitive to humidity and react with moisture to generate harmful hydrogen sulfide gas when exposed to air, requiring strict water-free and oxygen-free environment for material preparation and processing. In addition, in order to improve the interface contact between lithium metal and sulfide electrolytes, complex processes are usually required, such as interface modification, protective layer design, and pressure control, which increases the difficulty and cost of manufacturing.

[0006] In general, these problems jointly limit the practical application of sulfide solid electrolyte and lithium metal anode system, and further optimization of materials and interface engineering is needed. The interface between solid electrolyte and lithium metal anode is prone to chemical reaction, resulting in interface instability and forming an interface layer with high impedance, which affects the overall performance of the battery. Secondly, the solid electrolyte has weak lithium dendrite suppression ability at high current density and cannot meet the requirements of high rate charge and discharge.

[0007] In view of this, the present invention aims to design a novel multifunctional composite solid electrolyte prepared by finely mixing a variety of different solid electrolytes. The composite solid electrolyte not only retains the advantages of each material, but also improves the inhibition ability of lithium dendrites and interface stability through their synergistic effect. Experimental results show that the lithium battery using the mixed electrolyte exhibits excellent stability and long cycle performance under high current density conditions, and can still maintain a high capacity after multiple cycles. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a composite solid electrolyte and an all-solid-state battery and a 3D printed soft-pack battery containing the same. The composite solid electrolyte not only retains the respective advantages of the two materials, but also improves the inhibition ability and interface stability of lithium dendrites through synergistic effects, so that the lithium battery exhibits excellent stability and long cycle performance under high current density conditions, so as to solve the corresponding technical problems raised in the above background technology.

[0009] In order to achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention relates to a composite solid electrolyte, and the composite solid electrolyte (M-CSE) comprises the following components: LPSCl, LSiSnPSBrO.

[0010] Preferably, the mass fraction of the LSiSnPSBrO is 10wt%-30wt%.

[0011] Preferably, the mass fraction of the LSiSnPSBrO is 10wt%.

[0012] Preferably, the LPSCl is Li 5.3 PS 4.3 Cl 1.7 , the LSiSnPSBrO is Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO.

[0013] In a second aspect, the present invention relates to a method for preparing a composite solid electrolyte, wherein the preparation method is as follows: LPSCl and LSiSnPSBrO powders are manually ground in an agate mortar at a required mass ratio for 10 minutes or ball-milled in a planetary ball mill at a required mass ratio for 10 minutes to obtain the composite solid electrolyte (M-CSE).

[0014] In a third aspect, the present invention relates to an all-solid-state battery, comprising a negative electrode, an M-CSE layer, and a positive electrode, wherein the M-CSE layer is made of a composite solid electrolyte.

[0015] Preferably, the positive electrode is a composite positive electrode, and the preparation method of the composite positive electrode is: the positive electrode material is obtained by ball milling LCO, VGCF and LPSCl in a mass ratio of 60:5:35 at a rotation speed of 100 rpm for 0.2 h.

[0016] Preferably, the LPSCl is Li6PS5Cl.

[0017] Preferably, the preparation method of Li6PS5Cl is: mix Li2S, P2S5 and LiCl in a molar ratio of 5:1:2, set the rotation speed to 600 rpm, and ball mill for 12 hours; sinter at 550°C for 12 hours under argon atmosphere with a heating rate of 5°C / min, and finally crush to obtain Li6PS5Cl.

[0018] Preferably, there is a SE layer between the positive electrode and the M-CSE layer, and the SE layer is composed of Li6PS5Cl or Li 5.3 PS 4.3 Cl 1.7 Made.

[0019] In a fourth aspect, the present invention relates to a method for preparing an all-solid-state battery, the method comprising the following steps: (1) adding 60 mg of Li6PS5Cl or Li 5.3 PS 4.3 Cl 1.7 The SE layer was formed by pressing the pellets into a 10 mm diameter pellets under a pressure of 124 MPa.

[0020] (2) Place 10 mg of the composite positive electrode on one side of the SE layer and press at a pressure of 496 MPa for 2 minutes to make the two fit tightly together.

[0021] (3) 20 mg of pre-synthesized M-CSE was placed on the other side of the SE layer and pressed at a pressure of 868 MPa for 2 min to form an M-CSE layer, which was tightly bonded to the SE layer.

[0022] (4) A 10 mm lithium sheet is placed on the other side of the M-CSE layer. The lithium sheet is a lithium metal negative electrode, and the all-solid-state battery is assembled.

[0023] The M-CSE material is the composite solid electrolyte.

[0024] In a fifth aspect, the present invention relates to a method for preparing a 3D printed soft-pack battery, the preparation method comprising the following steps: step S1, taking a certain amount of composite positive electrode, negative electrode, electrolyte and M-CSE materials; adding 8% by mass of nitrile rubber (NBR) to the composite positive electrode, electrolyte and M-CSE respectively to form positive electrode printing slurry, electrolyte printing slurry and M-CSE printing slurry.

[0025] Step S2: Place the positive electrode printing slurry, electrolyte printing slurry and M-CSE printing slurry in multiple nozzles of the 3D printer respectively, and print M-CSE, electrolyte and composite positive electrode on the negative electrode in sequence by switching the nozzles.

[0026] Step S3: adding an aluminum-plastic film to the outside of the printed battery structure to complete the packaging.

[0027] Step S4: isostatically compact the battery at 2 MP to obtain a 3D printed soft-pack battery.

[0028] The preparation method of the composite positive electrode is as follows: the positive electrode material is obtained by ball milling LCO, VGCF and LPSCl with a mass ratio of 60:5:35 at a rotation speed of 100 rpm for 0.2 h.

[0029] The negative electrode is a copper-lithium composite strip, wherein the thickness of the lithium strip is 20 μm, and the thickness of the copper strip is 20 μm.

[0030] The electrolyte is Li 5.3 PS 4.3 Cl 1.7 .

[0031] The M-CSE material is the composite solid electrolyte.

[0032] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In the technical solution of the present invention, one of the cores is that when the M-CSE layer is present in the battery of the present invention, the stability and reliability of the battery performance can be effectively improved, especially under the conditions of high current density and long cycle life. The M-CSE layer inherits its advantages such as high chemical stability and good interface affinity. This not only protects the electrode material from the influence of corrosive side reactions, but also provides a smooth channel for lithium ion conduction. In addition, local interface passivation occurs, thereby reducing the stress caused by volume change and maintaining the compactness and stability of the interface. The interface passivation effect further inhibits the decomposition of the electrolyte and effectively slows down the growth of lithium dendrites. In addition, the lithium ion conductive material (such as Li-Sn alloy) in the M-CSE layer contributes to uniform lithium deposition and ensures uniform electric field distribution, thereby guiding the stable nucleation and growth of lithium. Therefore, through the dual regulation mechanism of physical isolation and chemical balance, the M-CSE layer can effectively inhibit the growth of lithium dendrites and prevent them from penetrating the solid electrolyte; the introduction of the M-CSE layer in the battery significantly improves its critical current density (CCD), allowing it to exhibit excellent electrochemical stability even at high current density. Through the combined effects of physical barrier properties and chemical stability, the M-CSE layer provides substantial protection for the battery, thereby improving its overall performance and extending its service life.

[0033] 2. In the technical solution of the present invention, the second core lies in: the M-CSE structure in the present invention is designed to enhance the interfacial stability between the lithium metal anode and the sulfide SSE. This structure ensures uniform lithium deposition and inhibits the formation of lithium dendrites, making it effective under the working conditions of all-solid-state batteries. More importantly, this structure was successfully implemented in 3D-printed sulfide-based solid-state batteries. Generally, sulfide electrolytes (such as LPSCl and Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO) is not completely consistent with the thermodynamic stability of lithium metal. When used independently, these electrolytes tend to form two suboptimal interfaces, namely SEI and MCI. This not only leads to interfacial degradation, but also allows lithium dendrite penetration, ultimately affecting battery performance. However, the M-CSE structure exhibits excellent interfacial stability, and its excellent performance is attributed to the internal inhibition mechanism. During the decomposition of the electrolyte, the internal expansion stress exerts a compressive force on the adjacent electrolyte, effectively inhibiting further decomposition. This self-limiting behavior helps to form a thin and dense interfacial layer, significantly reducing the interfacial impedance and preventing lithium dendrite penetration. Li 9.54 [Si 0.5 Sn 0.5]The decomposition of PSBrO not only produces metastable electrolyte particles, but also leads to the formation of lithiophilic Li-Si / Sn alloys. These alloys act as lithiophilic seeds in M-CSE, enhancing lithium kinetics and regulating lithium nucleation, leading to uniform lithium deposition. This dynamically stable M-CSE interface structure helps to balance the electric field and optimize lithium deposition, significantly improving the overall performance of the battery.

[0034] 3. The advantages of the present invention are: thanks to the M-CSE structure in the present invention, by exploring the high adaptability of sulfide-based SSE and combining the unique advantages of different electrolyte types, and combining advanced design with 3D printing technology, it opens up new possibilities for developing next-generation solid electrolyte materials to meet the commercial needs of all-solid-state batteries. This simple and efficient 3D printing manufacturing method has laid a solid foundation for the large-scale production and application of all-solid-state batteries, and provides a key reference for the future development of battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1-Figure 3 Schematic diagram of the interface of batteries with different configurations, where Figure 1 For interfacially unstable cells, where the growing interfacial layer leads to a significant overpotential, Figure 2 For batteries with SEI interface, there is lithium dendrite penetration. Figure 3 A battery containing M-CSE.

[0036] Figure 4-Figure 11 is a microscopic image of the composite solid electrolyte (M-CSE) in the present invention, wherein Figure 4 This is a SEM cross-sectional image with a resolution of 200um. Figure 5 The SEM cross-sectional image and EDX image with a resolution of 10um are shown. Figure 6 The SEM cross-sectional image and EDX image with a resolution of 2um are shown. Figure 7 The SEM cross-sectional image and EDX image with a resolution of 7um are shown. Figure 8 This is a cross-sectional SEM image of the lithium metal and electrolyte contact side of the battery in Comparative Example 2 after being stationary for 40 hours. Fig. 9 This is a cross-sectional SEM image of the lithium metal and electrolyte contact side of the battery in Comparative Example 1 after being stationary for 40 hours. Fig.10 This is a cross-sectional SEM image (resolution 30 um) of the lithium metal contact side of the battery in Example 1 after 40 hours of rest. Fig.11 This is a cross-sectional SEM image (resolution 15 um) of the contact side between lithium metal and M-CSE of the battery in Example 1 after being stationary for 40 hours.

[0037] Figure 12-Figure 17 The critical current density (CCD) test results of the battery under different electrolyte configurations, where Fig.12This is the critical current density (CCD) test curve of the battery in comparative example 1. Fig.13 This is a critical current density (CCD) test curve of the battery in comparative example 2. Fig.14 is a critical current density (CCD) test curve of the battery in Example 3, Fig.15 is a critical current density (CCD) test curve of the battery in Example 2, Fig.16 is a critical current density (CCD) test curve of the battery in Example 1, Fig.17 It is a cycle stability test curve diagram of the batteries in Example 1, Example 2, and Example 3.

[0038] Figure 18-Figure 24 The rate performance and corresponding charge-discharge curve test results of the battery under different electrolyte configurations are shown in Figure 2. Fig.18 , Fig.19 , Fig. 20 is the rate performance test result, Fig.21 , Fig. 22 , Fig.23 , Fig.24 The charge and discharge curve test results.

[0039] Figure 25-Figure 30 The discharge capacity and coulombic efficiency of the battery under different electrolyte configurations and the corresponding charge and discharge curve test results are shown in Figure 2. Fig.25 , Fig.26 , Fig. 27 The discharge capacity and coulombic efficiency test results of the battery at 0.5C rate. Fig.28 , Fig.29 , Fig.30 The charge and discharge curve test results of the battery corresponding to different cycle numbers.

[0040] Figure 31-Figure 35 is the XPS spectrum of the composite solid electrolyte (M-CSE), where Fig.31 The CI2p region collected from the electrolyte interior and the M-CSE / Li interface, Fig.32 is the Sn3d region collected from the electrolyte interior and the M-CSE / Li interface, Fig.33 is the S2p region collected from the electrolyte interior and the M-CSE / Li interface, Fig.34 , Fig.35 XRD patterns and Raman spectra of M-CSE, LPSCI and LSiSnPSBrO, respectively.

[0041] Figure 36-Figure 41 The test results of solid-state battery charge and discharge performance under different surface capacities are shown below: Fig.36 The charge and discharge curves of LCO|LPSCl-M-CSE|Li batteries with different surface capacities are shown in Figure 2. Fig.37The charge and discharge curves of LCO|LPSCl-M-CSE|Li square prismatic soft-pack battery with a side length of 2 cm Fig.38 , Fig.39 , Fig.40 The surface capacity is 5 mAh cm −2 The charge-discharge curves, rate capability and cycle performance of the LCO|LPSCl-M-CSE|Li battery. Fig.41 Nyquist plots of LCO|LPSCl-M-CSE|Li battery after different cycle times.

[0042] Fig.42 Schematic diagram of the stacking pressure test of the all-solid-state battery in the present invention. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0045] A composite solid electrolyte, the composite solid electrolyte (M-CSE) comprises the following components: LPSCl, LSiSnPSBrO, the mass fraction of LSiSnPSBrO is 10wt%-30wt%; the LPSCl is Li 5.3 PS 4.3 Cl 1.7 , the LSiSnPSBrO is Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO.

[0046] The preparation method of the composite solid electrolyte is as follows: LPSCl and LSiSnPSBrO powders are manually ground in an agate mortar for 10 minutes or ball-milled in a planetary ball mill for 10 minutes according to the required mass ratio to obtain the composite solid electrolyte (M-CSE), which is referred to as M-CSE layer in the following examples. Unless otherwise specified, M-CSE refers to a layer containing 10 wt% Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO composite electrolyte.

[0047] The LCO positive electrode is a composite positive electrode, and the preparation method of the composite positive electrode is: the positive electrode material is obtained by ball milling LCO, VGCF and LPSCl with a mass ratio of 60:5:35 at a rotation speed of 100rpm for 0.2h; the LPSCl is Li6PS5Cl, and the preparation method of Li6PS5Cl is: Li2S, P2S5 and LiCl are mixed according to a molar ratio of 5:1:2, the rotation speed is set to 600rpm, and ball milling is performed for 12h; sintering is performed at 550°C for 12h under an argon atmosphere with a heating rate of 5°C / min, and finally crushing to obtain Li6PS5Cl.

[0048] Example 1: A method for preparing an all-solid-state battery, the method comprising the following steps: (1) pressing 60 mg of LiPSCl into a disc with a diameter of 10 mm at a pressure of 124 MPa to form an SE layer; the LPSCl is Li 5.3 PS 4.3 Cl 1.7 .

[0049] (2) 20 mg of M-CSE composite electrolyte was placed on each side of the SE layer and pressed at a pressure of 496 MPa for 2 minutes to make the three layers fit tightly together; the mass fraction of LSiSnPSBrO in the M-CSE composite electrolyte was 10 wt%.

[0050] (3) Place a Li sheet with a diameter of 10 mm and a thickness of 20 μm on both sides of the above (2) layer and press them at a pressure of 30 MPa for 2 minutes to make the two fit tightly together, completing the symmetrical battery assembly and obtaining the "Li|M-CSE-LPSCl-M-CSE|Li" battery.

[0051] Example 2: A method for preparing an all-solid-state battery, the method comprising the following steps: (1) pressing 60 mg of LiPSCl into a 10 mm diameter disc at a pressure of 124 MPa to form an SE layer; the LPSCl is Li 5.3 PS 4.3 Cl 1.7 .

[0052] (2) 20 mg of M-CSE composite electrolyte was placed on each side of the SE layer and pressed at a pressure of 496 MPa for 2 minutes to make the three layers fit tightly together; the mass fraction of LSiSnPSBrO in the M-CSE composite electrolyte was 20 wt%.

[0053] (3) Place a Li sheet with a diameter of 10 mm and a thickness of 20 μm on both sides of the above (2) layer and press them at a pressure of 30 MPa for 2 minutes to make the two fit tightly together, completing the symmetrical battery assembly and obtaining the "Li|M-CSE-LPSCl-M-CSE|Li" battery.

[0054] Example 3: A method for preparing an all-solid-state battery, the method comprising the following steps: (1) pressing 60 mg of LiPSCl into a disc with a diameter of 10 mm at a pressure of 124 MPa to form an SE layer; the LPSCl is Li 5.3 PS 4.3 Cl 1.7 .

[0055] (2) 20 mg of M-CSE composite electrolyte was placed on each side of the SE layer and pressed at a pressure of 496 MPa for 2 minutes to make the three layers fit tightly together; the mass fraction of LSiSnPSBrO in the M-CSE composite electrolyte was 30 wt%.

[0056] (3) Place a Li sheet with a diameter of 10 mm and a thickness of 20 μm on both sides of the above (2) layer and press them at a pressure of 30 MPa for 2 minutes to make the two fit tightly together, completing the symmetrical battery assembly and obtaining the "Li|M-CSE-LPSCl-M-CSE|Li" battery.

[0057] Example 4: A method for preparing an all-solid-state battery, the method comprising the following steps: (1) adding 60 mg of Li 5.3 PS 4.3 Cl 1.7 The SE layer was formed by pressing the pellets into a 10 mm diameter pellets under a pressure of 124 MPa.

[0058] (2) Place 10 mg of LCO positive electrode on one side of the SE layer and press at a pressure of 496 MPa for 2 minutes to make the two fit tightly together.

[0059] (3) 20 mg of pre-synthesized M-CSE was placed on the other side of the SE layer and pressed at a pressure of 868 MPa for 2 min to form an M-CSE layer, wherein the M-CSE layer was tightly bonded to the SE layer; the mass fraction of LSiSnPSBrO in the M-CSE composite electrolyte was 10 wt%.

[0060] (4) A 10 mm lithium sheet is placed on the other side of the M-CSE layer. The lithium sheet is a lithium metal negative electrode. The all-solid-state battery is assembled and the "LCO / Li 5.3 PS 4.3 Cl 1.7 -M-CSE / Li” battery.

[0061] Example 5: A method for preparing an all-solid-state battery, the method comprising the following steps: (1) adding 60 mg of Li 5.5 PS 4.5 Cl 1.5The SE layer was formed by pressing the pellets into a 10 mm diameter pellets under a pressure of 124 MPa.

[0062] (2) Place 10 mg of LCO positive electrode on one side of the SE layer and press at a pressure of 496 MPa for 2 minutes to make the two fit tightly together.

[0063] (3) 20 mg of pre-synthesized M-CSE was placed on the other side of the SE layer and pressed at a pressure of 868 MPa for 2 min to form an M-CSE layer, wherein the M-CSE layer was tightly bonded to the SE layer; the mass fraction of LSiSnPSBrO in the M-CSE composite electrolyte was 10 wt%.

[0064] (4) A 10 mm lithium sheet is placed on the other side of the M-CSE layer. The lithium sheet is a lithium metal negative electrode. The all-solid-state battery is assembled and the "LCO / Li 5.5 PS 4.5 Cl 1.5 -M-CSE / Li” battery.

[0065] Example 6: A method for preparing an all-solid-state battery, the method comprising the following steps: (1) pressing 60 mg of Li6PS5Cl into a disc with a diameter of 10 mm at a pressure of 124 MPa to form a SE layer.

[0066] (2) Place 10 mg of LCO positive electrode on one side of the SE layer and press at a pressure of 496 MPa for 2 minutes to make the two fit tightly together.

[0067] (3) 20 mg of pre-synthesized M-CSE was placed on the other side of the SE layer and pressed at a pressure of 868 MPa for 2 min to form an M-CSE layer, wherein the M-CSE layer was tightly bonded to the SE layer; the mass fraction of LSiSnPSBrO in the M-CSE composite electrolyte was 10 wt%.

[0068] (4) A 10 mm lithium sheet is placed on the other side of the M-CSE layer. The lithium sheet is a lithium metal negative electrode. The all-solid-state battery is assembled and a "LCO / Li6PS5Cl-M-CSE / Li" battery is obtained.

[0069] Embodiment 7: A preparation method of a 3D printed soft-pack battery, the preparation method comprising the following steps: Step S1, taking a certain amount of composite positive electrode, negative electrode, electrolyte and M-CSE material; then adding 8% by mass of nitrile rubber (NBR) to the composite positive electrode, electrolyte and M-CSE respectively to form positive electrode printing slurry, electrolyte printing slurry and M-CSE printing slurry.

[0070] Step S2: Place the positive electrode printing slurry, electrolyte printing slurry and M-CSE printing slurry in multiple nozzles of the 3D printer respectively, and print M-CSE, electrolyte and composite positive electrode on the negative electrode in sequence by switching the nozzles.

[0071] Step S3: Add aluminum-plastic film to the printed battery structure to complete the packaging.

[0072] Step S4: isostatically compacting at 2MP to obtain a solid-state battery.

[0073] The preparation method of the composite positive electrode is as follows: the positive electrode material is obtained by ball milling LCO, VGCF and LPSCl with a mass ratio of 60:5:35 at a rotation speed of 100 rpm for 0.2 h.

[0074] The negative electrode is a copper-lithium composite strip, wherein the thickness of the lithium strip is 20 μm, and the thickness of the copper strip is 20 μm.

[0075] The electrolyte is Li 5.3 PS 4.3 Cl 1.7 .

[0076] The M-CSE material is the composite solid electrolyte.

[0077] Comparative Example 1: A method for preparing an all-solid-state battery, the method comprising the following steps: (1) pressing 60 mg of LSiSnPSBrO into a disc with a diameter of 10 mm at a pressure of 124 MPa to form an SE layer; the LSiSnPSBrO is Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO.

[0078] (2) Li sheets with a diameter of 10 mm and a thickness of 20 um were placed on both sides of the SE layer and pressed at a pressure of 30 MPa for 2 minutes to make the two fit tightly together, completing the symmetrical battery assembly and obtaining a "Li / LSiSnPSBrO / Li" battery.

[0079] Comparative Example 2: A method for preparing an all-solid-state battery, the method comprising the following steps: (1) adding 60 mg of Li 5.3 PS 4.3 Cl 1.7 The SE layer was formed by pressing the pellets into a 10 mm diameter pellets under a pressure of 124 MPa.

[0080] (2) Place a Li sheet with a diameter of 10 mm and a thickness of 20 μm on each side of the SE layer and press them at a pressure of 30 MPa for 2 minutes to make them fit tightly together, completing the symmetrical battery assembly and obtaining a "Li / Li 5.3 PS4.3 Cl 1.7 / Li" battery.

[0081] Through the description of the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 2, the following conclusions are drawn: The prior art publicly shows that in sulfide-based solid-state batteries, due to the thermodynamic instability between the sulfide electrolyte and the lithium metal, a decomposition reaction may occur when they come into contact, producing unwanted byproducts, which are generally referred to as mixed conductive interface (MCI) ( Figure 1 ). The above-mentioned mixed conductive interface (MCI) affects the transmission of lithium ions and the stability of the interface to a certain extent. The use of sulfide solid electrolytes alone will cause the electrolyte to continue to decompose at the interface, resulting in an unstable MCI layer. The MCI layer tends to thicken over time and become an ion insulating layer, which hinders the effective transmission of lithium ions. In addition, when the electrolyte contacts the lithium metal anode, an irreversible reaction occurs to form a solid electrolyte interface (SEI) ( Figure 2 ). The uneven deposition of the SEI layer on the surface of lithium metal results in an uneven current density distribution. In areas with higher current density, lithium ions deposit faster and are more likely to form dendrites. This is because, in these localized areas, the rapid deposition of lithium metal leads to the formation of tips or protrusions that can evolve into lithium dendrites. Due to the brittleness of the SEI material, it is prone to cracking during the expansion and contraction of lithium metal.

[0082] When the SEI layer is broken, the exposed lithium metal directly contacts the electrolyte and forms a new SEI layer. At the same time, the deposition of lithium metal becomes uncontrollable, resulting in an irregular deposition structure, which further promotes the growth of lithium dendrites. In contrast, when M-CSE ( Figure 3 ), it can effectively improve the stability and reliability of battery performance, especially under conditions of high current density and long cycle life. The M-CSE layer inherits its advantages such as high chemical stability and good interface affinity. This not only protects the electrode material from corrosive side reactions, but also provides a smooth channel for lithium ion conduction. In addition, local interface passivation occurs, which alleviates the stress caused by volume change and maintains the compactness and stability of the interface.

[0083] The interfacial passivation effect further inhibits the decomposition of the electrolyte and effectively slows down the growth of lithium dendrites. In addition, the lithium ion conductive materials (such as Li-Sn alloy) in the M-CSE layer contribute to uniform lithium deposition and ensure uniform electric field distribution, thereby guiding the stable nucleation and growth of lithium. Therefore, through the dual regulation mechanism of physical isolation and chemical balance, the M-CSE layer can effectively inhibit the growth of lithium dendrites and prevent them from penetrating the solid electrolyte.

[0084] The introduction of the M-CSE layer in the battery significantly improves its critical current density (CCD), allowing it to exhibit excellent electrochemical stability even at high current densities. Through the combined effects of physical barrier properties and chemical stability, the M-CSE layer provides substantial protection for the battery, thereby improving its overall performance and extending its service life.

[0085] In order to verify and accurately illustrate the concept in the present invention, the present invention prepares a composite electrolyte by finely mixing two types of electrolytes. Through a series of design and screening processes, the present invention selects Li 5.3 PS 4.3 Cl 1.7 and Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO, these two electrolytes were studied in depth.

[0086] In order to demonstrate the uniformity of the composite electrolyte layer, the composite electrolyte of the present invention was cold pressed at 250 MPa, and the low magnification cross-sectional SEM image ( Figure 4 , resolution 200um), the composite electrolyte layer shows densely packed particles with no visible cracks. At higher magnification ( Figure 5 , resolution 10um; Figure 6 , resolution 2um; Figure 7 , resolution 7um), two different morphological regions can be clearly observed. The finely mixed electrolyte shows one region with large particles, about tens of microns in size, and another region with small particles aggregated in clusters, typically a few microns in size. The two types of electrolytes are tightly compressed together. In addition, energy dispersive X-ray spectroscopy (EDX) analysis ( Figure 5 ) confirmed that the large particle area contains a lot of Cl, while the small particle area is rich in Sn, further indicating that the former is Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO, the latter is Li 5.3 PS 4.3 Cl 1.7 ; Figure 5 The purple part is the electrolyte Li 5.3 PS 4.3 Cl 1.7 , the blue part is the electrolyte Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO.

[0087] In addition, in order to study the stability of different electrolytes and lithium metal, the symmetrical battery made of three different sulfide electrolytes in the present invention was left stationary for 40 hours. The side cross-sectional SEM images of the lithium metal and electrolyte contact are as follows: Li / Li 5.3 PS 4.3 Cl 1.7 / Li (Comparative Example 1), Li / Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO / Li (Comparative Example 2) and Li|M-CSE-LPSCl-M-CSE|Li (Example 1) are three symmetrical lithium batteries with different electrolyte structures. 9.54 [Si 0.5 Sn 0.5 ]PSBrO electrolyte undergoes continuous interfacial degradation reactions with lithium metal, resulting in continuous decomposition of the electrolyte and the formation of a degraded MCI layer ( Figure 8 , Li / Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO / Li (Comparative Example 2) symmetrical battery after 40 hours of resting. The side cross-sectional SEM image of the lithium metal and electrolyte contact. 5.3 PS 4.3 Cl 1.7 In the case of the conventional silver-based sulfide electrolyte, non-uniform growth of lithium dendrites was observed at the interface due to the presence of a non-uniform interfacial reaction layer and electrochemical polarization, leading to further expansion of the dendrites ( Fig. 9 , Li / Li 5.3 PS 4.3 Cl 1.7 / Li (Comparative Example 1) symmetrical battery after 40 hours of rest (SEM image of the lithium metal and electrolyte contact side). In contrast, M-CSE exhibits excellent interfacial stability during lithium deposition ( Fig.10 , Fig.11 , Cross-sectional SEM images of the lithium metal contact side of the symmetric cell Li|M-CSE-LPSCl-M-CSE|Li (Example 1) at different magnifications after 40 hours of rest), which can be attributed to its unique in-situ lithophilic interface properties, providing a uniform lithium deposition pathway and suppressing stress at the interface by passivation.

[0088] Furthermore, in order to verify the effect of electrolyte on the critical current density (CCD) of the battery, the present invention adopts Li / Li 5.3 PS 4.3 Cl 1.7 / Li (Comparative Example 1), Li / Li 9.54 [Si 0.5 Sn 0.5]PSBrO / Li (Comparative Example 2), Li|M-CSE-LPSCl-M-CSE|Li (Example 1) three symmetric lithium batteries with different electrolyte structures were used to study the difference in their critical current density (CCD).

[0089] Specifically, the critical current density refers to the maximum current density that the lithium metal electrode can carry in this battery structure. When this value is exceeded, the lithium metal may nucleate and grow dendrites, resulting in a decrease in battery performance or even a short circuit.

[0090] The cycling stability of solid-state lithium metal symmetric batteries at a specific current density is a crucial performance indicator that is directly related to the safety, reliability and long life of the battery. In particular, in solid-state batteries, the deposition and desorption behavior of lithium metal electrodes, interface stability and current density management all determine the cycling stability of the battery.

[0091] Figure 12-Figure 17 Displays the CCD test results. Li / Li 5.3 PS 4.3 Cl 1.7 / Li (Comparative Example 1) in a symmetrical cell at 2.16 mA cm -2 The CCD is short-circuited ( Fig.12 ), indicating that the refined single electrolyte Li 5.3 PS 4.3 Cl 1.7 In contrast, Li / Li 9.54 [Si 0.5 Sn 0.5 The symmetric cell in PSBrO / Li (Comparative Example 2) is 0.66 mA cm -2 Short circuit at lower current density ( Fig.13 ), indicating that its stability with lithium metal needs to be further improved.

[0092] Notably, the optimized hybrid M-CSE (Li|M-CSE-LPSCl-M-CSE|Li (Example 1)) achieves an impressive 3.76 mA cm in a symmetric Li metal cell. -2 CCD( Fig.16 ), which is significantly enhanced compared with a single electrolyte.

[0093] In addition, the performance of M-CSE under different compositions was studied. -2 Li / Li 5.3 PS 4.3 Cl 1.7 / Li (Comparative Example 1).

[0094] Li / M-CSEwith10,wt%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO-Li 5.3 PS 4.3 Cl 1.7 -M-CSEwith10,wt%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO / Li (Example 1).

[0095] Li / M-CSEwith20,wt%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO-Li 5.3 PS 4.3 Cl 1.7 -M-CSEwith20,wt%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO / Li (Example 2).

[0096] Li / M-CSEwith30,wt%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO-Li 5.3 PS 4.3 Cl 1.7 -M-CSEwith30,wt%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO / Li (Example 3).

[0097] Cycling stability analysis of four symmetrical batteries.

[0098] As shown in the figure, increasing Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO electrolyte content leads to a decrease in CCD ( Fig.14 , Fig.15 , Fig.17 ). Therefore, the optimal composition was determined to contain 10wt%Li 9.54 [Si 0.5 Sn 0.5 ]M-CSE of PSBrO. The higher CCD value indicates that the growth of lithium dendrites is effectively suppressed, confirming the effectiveness of the electrolyte design. Fig.17 Further comparison was made at 1.5 mA cm -2 At a current density of 1.3 Å, a single electrolyte Li 5.3PS 4.3 Cl 1.7 (Comparative Example 1) and M-CSE battery long-term cycling stability. Single electrolyte Li 5.3 PS 4.3 Cl 1.7 (Comparative Example 1) short circuit occurred after 20 hours, while 10wt%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO M-CSE (Example 1) maintains stable cycling after 650 h of plating / stripping. 9.54 [Si 0.5 Sn 0.5 ] The M-CSE with 20wt% (Example 2) and 30wt% (Example 3) PSBrO shorted after 130h and 475h. These results further emphasize that 10wt% Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO M-CSE has excellent plating / stripping performance and dendrite suppression ability.

[0099] Furthermore, to verify the wide applicability of M-CSE, all-solid-state batteries (ASSLMBs) were fabricated using lithium metal anode, various sulfide electrolytes, M-CSE, and LCO cathode. The rate performance of a battery reflects its power output and charging efficiency, making it a key step in the development and evaluation of battery technology. Figure 18-Figure 24 It shows that when the current rate is increased from 0.1C (0.05mAcm -2 ) are gradually increased to 0.2C, 0.5C, 1C, 2C and 5C. All batteries were tested between 2.5V and 4.2V.

[0100] like Fig.18 As shown, LCO|Li6PS5Cl|Li, LCO|Li 5.5 PS 4.5 Cl 1.5 |Li、LCO|Li 5.3 PS 4.3 ClBr 0.7 |Li、LCO|Li 5.3 PS 4.3 Cl 1.7 |Li four groups of battery configurations were experimentally compared. In the all-solid-state battery (ASSLMB) without M-CSE, only LCO|Li 5.3 PS 4.3 ClBr 0.7| The Li configuration has no short circuit at 5C, but its reversible specific capacity at 5C is only 86.7 mAhg -1 , which is a large deviation from the theoretical specific capacity of the LCO cathode. For other all-solid-state batteries (ASSLMBs) without M-CSE, their rate performance is even worse, with short circuits occurring between 0.2C and 1C, indicating poor rate capability.

[0101] like Fig.19 As shown, LCO|Li6PS5Cl-M-CSE|Li (Example 6), LCO|Li 5.5 PS 4.5 Cl 1.5 -M-CSE|Li (Example 5), LCO|Li 5.3 PS 4.3 ClBr 0.7 -M-CSE|Li, LCO|Li 5.3 PS 4.3 Cl 1.7 -M-CSE|Li (Example 4) Four groups of battery configurations were compared experimentally. After adding M-CSE to the electrolyte, the rate performance of the battery showed significant improvement. For the configuration with the best performance, LCO|Li 5.5 PS 4.5 Cl 1.5 -M-CSE|Li, the battery exhibits very low polarization and achieves 163.7 mAh g at a low rate of 0.1C -1 As the rate increases to 0.2C, 0.5C, 1C, 2C and 5C, the reversible specific capacity gradually decreases to 162.9, 159.5, 155.7, 150 and 138.7 mAh g, respectively. -1 . This demonstrates the excellent reversible capacity and capacity retention at high rates. In addition, after 5 charge-discharge cycles at 5C, the reversible capacity at 2C was almost completely restored to its original level when the battery was tested again at a lower rate. This phenomenon indicates that the all-solid-state battery (ASSLMB) with M-CSE exhibits excellent reversibility and excellent performance under high-rate conditions. In addition, it also shows that the in-situ protective layer formed by M-CSE suppresses the growth of lithium dendrites, enabling the all-solid-state battery (ASSLMB) to withstand high current conditions.

[0102] like Fig. 20 As shown in the figure, the rate performance of all-solid-state batteries (ASSLMBs) with different M-CSE ratios was studied, especially M-CSE (10%, 20%, 30%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO).

[0103] Fig. 20 The battery structure adopts LCO / Li 5.3 PS 4.3 Cl 1.7 -M-CSE / Li. Since M-CSE is composed of two electrolytes Li 5.3 PS 4.3 Cl 1.7 and Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO is mixed in a certain proportion. Fig. 20 In order to explore the ratio of the two electrolytes, the M-CSE has better performance. 9.54 [Si 0.5 Sn 0.5 ]PSBrO means that the mass ratio of Li in M-CSE 5.3 PS 4.3 Cl 1.7 :Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO=9:1. And so on, 20%%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO is 8:2, 30%%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO is 7:3, 0%%Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO is 10:0. Fig. 20 When M-CSE is mentioned elsewhere, it is assumed that M-CSE stands for Li 5.3 PS 4.3 Cl 1.7 :Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO=9:1.

[0104] Meanwhile, further explanation is as follows: the electrolyte in the present invention, wherein Li 5.3 PS 4.3 ClBr 0.7 It is doped with Br element. The electrolyte Li 5.3 PS 4.3 Cl 1.7 and Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 These three electrolytes are not doped with Br, and their essential difference lies in the different Cl element contents.

[0105] The results show that as Li 9.54 [Si 0.5 Sn 0.5 ]With the increase of PSBrO content, the discharge capacity at 5C gradually decreased to 133.4, 86.7 and 80.1 mAh g, respectively. -1 This decrease is attributed to the increase in Li 9.54 [Si 0.5 Sn 0.5 ]With the increase of PSBrO content, the dynamic stability of the interfacial layer formed by interfacial passivation is destroyed, resulting in a larger polarization due to the side reactions between lithium metal and solid electrolyte (SE).

[0106] like Fig.21 , Fig. 22 , Fig.23 , Fig.24 As shown, using: LCO|Li6PS5Cl-M-CSE|Li, LCO|Li 5.5 PS 4.5 Cl 1.5 -M-CSE|Li, LCO|Li 5.3 PS 4.3 ClBr 0.7 -M-CSE|Li, LCO|Li 5.3 PS 4.3 Cl 1.7 -M-CSE|Li four groups of battery configurations were experimentally compared, and the charge and discharge curves after adding M-CSE.

[0107] Furthermore, in order to verify the wide applicability of M-CSE, Figure 25-Figure 30 The long-cycle performance and corresponding Coulombic efficiency of all-solid-state batteries (ASSLMBs) fabricated from Li metal anode, various sulfide electrolytes, M-CSE, and LCO cathode are shown.

[0108] like Fig.25 , using LCO|Li 5.5 PS 4.5 ClBr 1.5 |Li、LCO|Li 5.5 PS 4.5 ClBr 1.5 -M-CSE|Li was used to compare the cycle life performance and capacity attenuation performance of the battery without and with M-CSE. Specifically, at a rate of 0.5C (surface capacity of 0.98 mAh cm -2 )’s discharge capacity and Coulombic efficiency.

[0109] like Fig.26 , using LCO|Li 5.3 PS4.3 Cl 1.7 |Li、LCO|Li 5.3 PS 4.3 Cl 1.7 -M-CSE|Li was used to compare the cycle life performance and capacity attenuation performance of the battery without and with M-CSE. Specifically, at a rate of 0.5C (surface capacity of 0.98 mAh cm -2 )’s discharge capacity and Coulombic efficiency.

[0110] As shown in 27, LCO|Li6PS5Cl|Li and LCO|Li6PS5Cl-M-CSE|Li were used to compare the cycle life performance and capacity attenuation performance of the battery without adding M-CSE and with adding M-CSE. Specifically, at a rate of 0.5C (surface capacity of 0.98 mAh cm -2 )’s discharge capacity and Coulombic efficiency.

[0111] As shown in 28, LCO|Li 5.5 PS 4.5 ClBr 1.5 |Li、LCO|Li 5.5 PS 4.5 ClBr 1.5 -M-CSE|Li compares the cycle life performance and capacity decay performance of the battery without and with M-CSE, specifically the charge and discharge curves corresponding to different cycle numbers.

[0112] As shown in 29, LCO|Li 5.3 PS 4.3 Cl 1.7 |Li、LCO|Li 5.3 PS 4.3 Cl 1.7 -M-CSE|Li compares the cycle life performance and capacity decay performance of the battery without and with M-CSE, specifically the charge and discharge curves corresponding to different cycle numbers.

[0113] As shown in Figure 30, LCO|Li6PS5Cl|Li and LCO|Li6PS5Cl-M-CSE|Li were used to compare the cycle life performance and capacity decay performance of batteries without adding M-CSE and with adding M-CSE, specifically the charge and discharge curves corresponding to different cycle numbers.

[0114] The results show that the battery with the addition of M-CSE exhibits a longer cycle life and lower capacity decay during cycling at 0.5C. 5.5 PS 4.5 ClBr 1.5-M-CSE|Li full battery at 0.5C (1mAcm -2 ) After 250 cycles, it still maintains 134.5mAhg -1 The discharge specific capacity, capacity retention rate is 90.1%, and Coulomb efficiency is 99.91%.

[0115] Likewise, Fig.26 As shown, LCO / Li 5.3 PS 4.3 Cl 1.7 -M-CSE / Li battery still maintains 133.3mAhg after 300 cycles at 0.5C -1 The discharge specific capacity, capacity retention rate is 90.2%, and Coulomb efficiency is 99.92%.

[0116] Even more impressive is that Fig. 27 As shown in Figure 2, the LCO / Li6PS5Cl-M-CSE / Li battery exhibits better performance, maintaining 124.3 mAh g after 500 cycles. −1 The discharge capacity of the battery was 2.387 W with a capacity retention rate of 95.04%, representing a major breakthrough in electrochemical performance.

[0117] In comparison, the battery without adding M-CSE exhibited lower reversible capacity and poor cycling performance, while the battery with adding M-CSE exhibited higher reversible capacity and better cycling performance.

[0118] Specifically, the discharge capacities of the LCO / Li6PS5Cl-M-CSE / Li battery at the 100th, 200th, 300th, and 500th cycles were 126.6, 125.8, 125.3, and 124.3 mAh g, respectively. -1 (like Fig.30 ).

[0119] LCO|Li 5.3 PS 4.3 Cl 1.7 -M-CSE|Li battery exhibited 141.1 and 133.3 mAh g at the 150th and 300th cycles, respectively. -1 The discharge capacity (such as Fig.29 ).

[0120] LCO|Li 5.5 PS 4.5 ClBr 1.5 The discharge capacities of the M-CSE|Li battery at the 150th and 250th cycles were 136.1 and 134.5 mAh g, respectively. -1 (like Fig.28 ).

[0121] At the same time, in order to verify the state of the composite solid electrolyte (M-CSE) after mixing, XPS spectrum of the M-CSE electrolyte was collected.

[0122] For the spectrum collected at the M-CSE / Li interface, an additional peak was observed at 54.8 eV, which was attributed to Li0. This peak comes from the interfacial reaction products, especially the Li-Sn / Si alloy, and the lithium adhering to the surface. Fig.31 As shown, the S2p spectrum collected from inside the M-CSE electrolyte does not change significantly before and after cycling, showing two peaks at 162.6 eV and 161.4 eV, attributed to SnS43- and PS43-. In contrast, after cycling, the spectrum collected at the M-CSE / Li interface exhibits two peaks corresponding to Li2S (161.3 eV and 160.2 eV), indicating that the M-CSE electrolyte is significantly lithiated. This suggests that in the M-CSE electrolyte, decomposition mainly occurs at the interface and is well suppressed within the electrolyte. Similar conclusions can be drawn from the P2p spectrum (such as Fig.32 The initial spectrum shows P2p peaks at 132.6 eV and 131.8 eV, attributed to SnS43- and PS43-. After cycling, the spectrum collected from the interior shows almost the same signals, while the spectrum collected at the interface shows additional peaks at 128.6 eV and 127.9 eV, corresponding to the electrolyte decomposition product Li3P. The Sn3d spectrum (as shown in Fig.33 As shown, ) shows that Li 9.54 [Si 0.5 Sn 0.5 ]Sn4+ exists in PSBrO. However, after cycling, the peak intensity in the Sn3d spectrum collected at the interface decreases significantly. In addition, new peaks appear at 491.7 eV and 483.5 eV, corresponding to Li-Sn alloys, indicating that Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO occurs at the M-CSE / Li interface. Fine XPS scans of Cl collected from the interior and the interface show no significant changes after cycling, confirming that Li 5.3 PS 4.3 Cl 1.7 According to the XPS results, it can be concluded that after rate cycling, Li 9.54 [Si 0.5 Sn 0.5 The decomposition of PSBrO is mainly confined to the M-CSE / Li interface. 9.54 [Si 0.5 Sn 0.5This limited decomposition of PSBrO serves to consume the lithium dendrites formed under high current while preventing the continued growth of a highly resistive interfacial layer.

[0123] XRD refinement further confirmed that the primary structure of the synthesized LiSiSnPSBrO is Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO. In addition, the sample contains 7.13wt% Li2SnS3 phase. Fig.34 As shown, by pre-synthesizing Li 5.3 PS 4.3 Cl 1.7 and Li 9.54 [Si 0.5 Sn 0.5 The superposition of ]PSBrO can well reproduce the XRD pattern of M-CSE, indicating that the two solid electrolytes are physically mixed in M-CSE.

[0124] like Fig.35 As shown, 200-550cm -1 Raman spectra of electrolyte powders in the wavenumber range. 9.54 [Si 0.5 Sn 0.5 ] The results of other reports on PSBrO are consistent with that at 422 cm -1 and 416cm -1 The strongest Raman peak at 346 cm is attributed to PS4 tetrahedron, while -1 The peak at 308 cm is attributed to SnS4 tetrahedron. -1 The peak at 422 cm corresponds to the SnS3 unit and is attributed to the impurity Li2SnS3. -1 The Raman spectrum of M-CSE is similar to that of the pre-synthesized Li 5.3 PS 4.3 Cl 1.7 and Li 9.54 [Si 0.5 Sn 0.5 The superposition of the PSBrO spectra further supports the conclusion that the two solid electrolytes are physically mixed without any chemical reaction.

[0125] Overall, the all-solid-state battery (ASSLMB) using M-CSE exhibits excellent electrochemical performance, providing strong feasibility support for the development of high specific surface area and type batteries in the future.

[0126] After adding M-CSE, the all-solid-state battery (ASSLMB) not only exhibits excellent rate and long-cycle performance, but also achieves extremely high areal capacity, such as Fig.36 As shown, LCO / Li 5.3 PS 4.3 Cl 1.7 -M-CSE / Li battery in 2, 5 and 10 mAhcm -2 The ultra-high surface capacity of 0.1C and 10mAhcm -2 When the battery shows 125.9 mAh g -1 The reversible specific capacity is remarkable considering such a high surface capacity. -2 The battery also exhibits excellent rate performance, maintaining about 100 mAh g at 2C. -1 The reversible specific capacity (such as Fig.38 , Fig.39 In addition, at 5mAhcm -2 The surface capacity and 1mAcm -2 After 50 cycles at a high current density, the reversible specific capacity retention rate is 90.8% (e.g. Fig.40 , Fig.41 ).

[0127] In view of the excellent performance of the all-solid-state battery (ASSLMB) under M-CSE and to demonstrate the practical application potential of this structure, the present invention uses a 3D printing method to assemble a square battery with a side length of 2 cm (Example 7). The active material content of the cathode is 70% and the surface loading is 20 mg cm -2 In the first discharge cycle, the battery achieved 128.92 mAh g -1 The specific capacity is up to 170Whkg -1 Energy density (energy density is calculated based on the total mass of battery materials, including cathode, electrolyte and anode) (such as Fig.37 The automated nature of 3D printing also provides a path for large-scale production of sulfide-based all-solid-state batteries. Under the ultra-low natural stacking pressure of 3D printing, the battery exhibits reduced expansion potential, maintains stable shape and function, and minimizes mechanical stress and fatigue within the internal material.

[0128] like Fig.42 Shown in the figure is a schematic diagram of the molded cell stack pressure test apparatus and battery configuration for an all-solid-state battery (ASSLMB).

[0129] Summary: This paper designs an M-CSE structure to enhance the interfacial stability between the lithium metal anode and the sulfide SSE. This structure ensures uniform lithium deposition and suppresses the formation of lithium dendrites, making it effective under the working conditions of all-solid-state batteries. More importantly, this paper has successfully implemented this structure in 3D-printed sulfide-based solid-state batteries. Generally, sulfide electrolytes (such as LPSCl and Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO) are not completely consistent with the thermodynamic stability of lithium metal. When used independently, these electrolytes tend to form two suboptimal interfaces, namely SEI and MCI. This not only leads to interfacial degradation, but also allows lithium dendrite penetration, ultimately affecting battery performance. However, the M-CSE structure exhibits excellent interfacial stability, and its excellent performance is attributed to the internal inhibition mechanism. During the electrolyte decomposition process, the internal expansion stress exerts a compressive force on the adjacent electrolyte, effectively inhibiting further decomposition. This self-limiting behavior helps to form a thin and dense interfacial layer, significantly reducing the interfacial impedance and preventing lithium dendrite penetration.

[0130] Li 9.54 [Si 0.5 Sn 0.5 ]The decomposition of PSBrO not only produces metastable electrolyte particles, but also leads to the formation of lithiophilic Li-Si / Sn alloys. These alloys act as lithiophilic seeds in M-CSE, enhancing lithium kinetics and regulating lithium nucleation, leading to uniform lithium deposition. This dynamically stable M-CSE interface structure helps to balance the electric field and optimize lithium deposition, significantly improving the overall performance of the battery.

[0131] The experimental results show that, thanks to the M-CSE structure, Li / M-CSE-Li 5.3 PS 4.3 Cl 1.7 -M-CSE / Li symmetric battery achieves up to 3.76mAcm -2 The CCD of the LCO / Li6PS5Cl-M-CSE / Li full cell was found to have a stable cycling performance of 650 hours. In addition, the LCO / Li6PS5Cl-M-CSE / Li full cell retained 95.04% of its capacity after 500 cycles at 0.5C. It is worth noting that a 3D printed square cell with a side length of 2 cm was assembled at ultra-low pressure, with a cathode active material ratio of 70% and a surface loading of 20 mg cm -2 The battery achieved 128.92mAhg -1 The specific first cycle discharge capacity provides up to 170Whkg -1 These findings provide valuable insights into the interfacial stability issues between Li metal anodes and sulfide SSEs.

[0132] In summary, this invention provides a new solution by exploring the high adaptability of sulfide-based SSE and combining the unique advantages of different electrolyte types. By combining advanced design with 3D printing technology, it opens up new possibilities for developing next-generation solid electrolyte materials to meet the commercial needs of all-solid-state batteries. This simple and efficient 3D printing manufacturing method lays a solid foundation for the large-scale production and application of all-solid-state batteries and provides a key reference for the future development of battery technology.

[0133] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite solid electrolyte, characterized in that: The composite solid electrolyte (M-CSE) includes the following components: LPSCl, LSiSnPSBrO.

2. The composite solid electrolyte according to claim 1, characterized in that The mass fraction of the LSiSnPSBrO is 10wt%-30wt%, preferably, the mass fraction of the LSiSnPSBrO is 10wt%.

3. The composite solid electrolyte according to claim 1 or 2, characterized in that: The LPSCl is Li 5.3 PS 4.3 Cl 1.7 , the LSiSnPSBrO is Li 9.54 [Si 0.5 Sn 0.5 ]PSBrO.

4. A method for preparing a composite solid electrolyte as claimed in any one of claims 1 to 3, characterized in that: The preparation method is as follows: LPSCl and LSiSnPSBrO powders are manually ground in an agate mortar for 10 minutes or ball-milled in a planetary ball mill for 10 minutes at a desired mass ratio to obtain the composite solid electrolyte (M-CSE).

5. An all-solid-state battery, characterized in that: The invention comprises a negative electrode, an M-CSE layer and a positive electrode, wherein the M-CSE layer is made of the composite solid electrolyte according to any one of claims 1 to 3.

6. The all-solid-state battery according to claim 5, characterized in that: The positive electrode is a composite positive electrode, and the preparation method of the composite positive electrode is: the positive electrode material is ball-milled LCO, VGCF and LPSCl with a mass ratio of 60:5:35 at a rotation speed of 100 rpm for 0.2 h, and the LPSCl is Li6PS5Cl.

7. The all-solid-state battery according to claim 6, characterized in that: The preparation method of Li6PS5Cl is as follows: Li2S, P2S5 and LiCl are mixed in a molar ratio of 5:1:2, the rotation speed is set to 600 rpm, and ball milling is performed for 12 hours; sintering is performed at 550° C. for 12 hours under an argon atmosphere with a heating rate of 5° C. / min, and finally crushing to obtain Li6PS5Cl.

8. The all-solid-state battery according to claim 7, characterized in that: There is a SE layer between the positive electrode and the M-CSE layer, and the SE layer is composed of Li6PS5Cl or Li 5.3 PS 4.3 Cl 1.7 Made.

9. A method for preparing an all-solid-state battery, characterized in that: The preparation method comprises the following steps: (1) adding 60 mg of Li6PS5Cl or Li 5.3 PS 4.3 Cl 1.7 The SE layer is formed by pressing into a disc with a diameter of 10 mm under a pressure of 124 MPa; (2) placing 10 mg of the composite positive electrode on one side of the SE layer and pressing at a pressure of 496 MPa for 2 minutes to make the two fit tightly; (3) placing 20 mg of the pre-synthesized M-CSE on the other side of the SE layer and pressing at a pressure of 868 MPa for 2 minutes to form an M-CSE layer, wherein the M-CSE layer is tightly combined with the SE layer; (4) placing a 10 mm lithium sheet on the other side of the M-CSE layer, wherein the lithium sheet is a lithium metal negative electrode, and the all-solid-state battery is assembled; the M-CSE material is the composite solid electrolyte described in any one of claims 1 to 3.

10. A method for preparing a 3D printed soft-pack battery, characterized in that: The preparation method comprises the following steps: step S1, taking a certain amount of composite positive electrode, negative electrode, electrolyte and M-CSE materials; adding 8% by mass of nitrile rubber (NBR) to the composite positive electrode, electrolyte and M-CSE to prepare positive electrode printing slurry, electrolyte printing slurry and M-CSE printing slurry; step S2, placing the positive electrode printing slurry, electrolyte printing slurry and M-CSE printing slurry in multiple nozzles of a 3D printer respectively, and printing M-CSE on the negative electrode in sequence by switching the nozzles; E, electrolyte, composite positive electrode; step S3, adding aluminum plastic film to the outside of the printed battery structure to complete the packaging; step S4, isostatic pressing at 2MP to obtain a 3D printed soft package battery; wherein the preparation method of the composite positive electrode is: the positive electrode material is ball milled LCO, VGCF and LPSCl, the mass ratio is 60:5:35, and the speed is 100rpm for 0.2h; the negative electrode is a copper-lithium composite belt, wherein the lithium belt thickness is 20μm, and the copper belt thickness is 20μm; the electrolyte is Li 5.3 PS 4.3 Cl 1.7 ; The M-CSE material is a composite solid electrolyte as described in any one of claims 1-3.

Citation Information

Patent Citations

  • Alloy / carbon composite film for all-solid-state battery and preparation method of alloy / carbon composite film

    CN115763706A